Transient Numerical Analysis of Single Heat Pipe Failure in Heat Pipe Reactor - HAN Ye1, , YANG Siyuan2, WEN Qinglong2, CHAI Baohua1, ZHANG Yakun1 (Yuanzineng kexue jishu)
As means to meet the needs of long-distance energy supply, safe power supply for remote areas facilities, power supply for the surface of the moon and Mars, and deep space and deep-sea exploration, the application of nuclear energy has attracted more and more attention, which has stimulated the development of a series of innovative reactor concepts. Among them, the heat pipe cooled reactor becomes a research hotspot in nuclear energy due to its simple and compact system and higher reliability and safety. The design goal of the heat pipe cooled reactor is to establish sufficient safety margin on the average heat pipe temperature. If a single heat pipe failure occurs, it should be ensured that the heat pipe conditions nearby do not exceed the maximum allowable temperature and power, thereby preventing the heat pipe cascade failure. In this study, the numerical simulation transient analysis of single heat pipe failure accident was carried out using ANSYS Mechanical APDL software. The temperature distribution of the fuel rod under three severe conditions was solved. The maximum temperature of the core center increases by 123.65 K, 124.15 K and 204.05 K respectively, and the maximum reaches 1 352.49 K, and reaches the extreme value at about 95 s, 105 s and 123 s respectively, entering a new steady state. By comparing the maximum temperature of the core center, the maximum working temperature of the heat pipe, the maximum temperature of the substrate and the time required to reach the new steady state under the three conditions, the conclusion that the central failure heat pipe is outside the core is obtained. Under the most severe conditions, the maximum temperature of the substrate is 1 314.16 K, the peak temperature of the core center reaches 1 352.49 K, and the peak operating temperature of the heat pipe is 1 149.84 K, which does not exceed the allowable operating temperature range and the material temperature limit. In addition, under this condition, the maximum peak heat flux of the No. 4 heat pipe reaches 83 709.87 W, and the maximum final heat flux of the No. 2 heat pipe reaches 7 0183.29 W. According to the heat transfer limit range of the heat pipe, it is determined that there is no risk of overall cascade failure. In this paper, a single heat pipe failure transient analysis model of heat pipe cooled reactor was established, and the heat pipe failure simulation test of heat pipe cooled reactor design was completed to evaluate the real transient thermal response to the fault, which lays a solid foundation for the improvement of core safety analysis and overall design.